The Relationship Between Maternal and Fetal Factors with Anorectal Malformations - Akbar, Puang Hafsari; Darussalam, Andi Husni Esa; Baharuddin, Baharuddin; Alasiry, Ema; Gani, Aziz Beru (Journal La Medihealtico, 2025)
Children with Anorectal Malformations (ARM) may experience lifelong physical impairment if not treated properly, and may adversely affect the personal and economic existence of affected individuals, as well as families and communities. The purpose of this study was to determine the factors of the incidence of anorectal malformations in neonates from maternal aspects and fetal aspects. By using research methods in the form of literature studies from the search results of 62 findings and 38 literature based on Electronic Based. The results of the discussion state that maternal risk factors that contribute to the incidence of ARM include exposure to teratogens such as cigarettes, alcohol, pesticides, drugs, and radiation during pregnancy. And fetal risk factors that contribute to the incidence of ARM include genetic and chromosomal factors, including related syndromes such as Down syndrome and VACTERL, which are the main causes of ARM.